Persepsi pelajar berisiko terhadap iklim pembelajaran - Wan Ali, Wan Zah; Md Nor, Sharifah; Salim, Siti Suria; Mohamed, Othman; Abu Bakar, Kamariah; Abd. Samad, Arshad; Hamzah, Ramlah; Ahmad Tarmizi, Rohani; Jamian, Rasid; Marzuki, Hayat (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2009)
Learning is a process which occurs in a social context. The streaming of students into academically weak classrooms creates a negative learning context or climate for teaching and learning. Therefore, the risk of failure increases among these students in their learning process. As such, it is important to understand the learning climate in these classrooms in order to overcome the problems of at-risk students. This paper attempts to highlight the findings of a study pertaining to perceptions of students toward their classroom learning climate, involving 1,689 form two students from 28 schools in Kuala Lumpur and Selangor. Data were gathered by utilizing the questionnaire and analyzed descriptively. The findings reveal that in general, students in the various streams perceive their classroom learning climate as moderate. However there is a significant difference in perceptions of students from the three streams studied, with regards to their teachers in terms of their treatment of students, their teaching approaches and their expectations of their students. High achievers have more positive perception towards their teachers, as compared to the low and extremely low achievers. Implications of the findings and some suggestions are also discussed.